As Kinderszenen de Almeida Prado: uma contribuição transdisciplinar à pedagogia pianística - Junia Canton Rocha (2024)
The object of this research was Almeida Prado's Kinderzsenen, a piano piece inspired by childhood. Its general objective was to identify and demonstrate the pedagogical potential of this work for the technical-pianistic and musical development of the student. The research falls within the scope of action research and crosscuts various themes, including: childhood and Almeida Prado's compositional and pedagogical aspects; piano technique; piano pedagogy; the biomechanics of performance and motivational and cognitive issues involved in the teaching- learning process of this instrument. By adopting a qualitative approach, the action research undertaken here included field research, when 87 piano lessons on the 18 Kinderszenen were given by the researcher to an 11-year-old student at the start of the research, who was practically a beginner at the piano. The research included the participation of a group of four cooperating researchers, all pianists with expertise in piano teaching, who observed the student's progress through videos of the lessons and made suggestions for improving his technical-pianistic and musical development. The results of this research pointed to: (1) the classification of pedagogical-musical strategies during the Kinderszenen teaching/learning process into five categories - technical-pianistic and musical strategies, analytical-formal strategies, musical reading strategies, pedaling strategies, and cognitive-motivational strategies; (2) the technical- pianistic, musical and cognitive improvement of the student during the research; (3) the complete recording of the work by the participating student and (4) the possibility of classifying, in order of pianistic and musical difficulty, the 18 Children's Scenes between intermediate and advanced levels. It was possible to conclude that this research allowed for a clearer and deeper understanding of how the Kinderszenen teaching-learning process, developed throughout the research, was able to promote the student's technical-pianistic and musical development. Five main factors were the threads that led the research successfully to its conclusion: (1) the motivation of the student and the researcher; (2) the development of the student's musical reading; (3) the pedagogical and musical potential inherent in the Kinderszenen; (4) knowledge about the biomechanics of performance; and (5) knowledge about musical cognition. We hope that this research, by publicizing and pointing out the pedagogical potential of Almeida Prado's Kinderszenen for piano, can contribute to the understanding of the numerous dimensions of piano pedagogy and enrich the repertoire options of teachers who intend to lead their students from intermediate to more advanced levels of piano performance.